Pengaruh Sabar dalam Mengatasi Stres pada Ibu Bekerja selama Pandemi Covid 19 - Nihayah, Zahrotun; Layyinah, Layyinah; Lubis, Nabila Nur'amalina; Mulyati, Sri; Shandika Puri, Valendra Granitha; Rahmani, Ima Sri (Psikis : Jurnal Psikologi Islami, 2023)
The phenomenon of Covid 19 pandemic that has been going on since 2020 has brought changes in our society, including the demands put on working mother that needs to help with household needs and working as employee as well. This study conducted to examine the effect of patience on working mother’s stress level during the Covid 19 pandemic. The sampling techniques used was non-probability samping with total respondents of 244 working mothers. Literature review was conducted in collecting data to build a foundation concept of patience in Islam and the construct validity was conducted with quantitative approach. The results showed a significant effect of patience on stress by 9% with significance value of 0.000 (p<0.05).